HADITH SEARCH TRENDS ON GOOGLE IN INDONESIA REFLECT SOCIO-POLITICAL INFLUENCES AND ITS IMPLICATIONS (2020-2024) - Monady, Hanief; Hilmy, Masdar; Erawati, Desi (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
In the digital era, the internet has become a primary source for the public in seeking religious knowledge, including Hadith. The trend of Hadith searches on Google reflects society’s responses to the socio-political dynamics occurring within a given period. This study aims to examine the patterns of Hadith searches on Google from 2020 to 2024 and analyze the socio-political factors influencing fluctuations in these trends. The urgency of this research lies in the importance of understanding how society utilizes Hadith as a reference in responding to emerging issues, as well as its implications for religious understanding in Indonesia. This study adopts a qualitative approach, employing historical methods and digital data analysis. Data on Hadith search trends were collected through Google Trends and analyzed based on the evolving thematic patterns that emerged annually. Subsequently, the socio-political factors influencing these trends were examined by referring to national events occurring during the same period. The findings reveal that Hadith search trends experienced significant increases during certain periods, particularly in connection with political events, government policies, and religious-social issues. Dominant search themes include leadership, social ethics, and tolerance, reflecting a societal demand for moral guidance in addressing socio-political challenges. These findings underscore that digitalization has transformed the way people access and interpret Hadith, highlighting the need for both digital and religious literacy to ensure accurate and contextual interpretations. [Dalam era digital, internet telah menjadi sumber utama bagi masyarakat dalam mencari informasi keagamaan, termasuk hadis. Tren pencarian hadis di Google mencerminkan respons masyarakat terhadap dinamika sosial-politik yang terjadi dalam suatu periode. Penelitian ini berupaya mengkaji pola pencarian hadis di Google selama tahun 2020-2024 serta menganalisis faktor sosial-politik yang memengaruhi fluktuasi tren tersebut. Urgensi penelitian ini terletak pada pentingnya memahami bagaimana masyarakat menggunakan hadis sebagai rujukan dalam merespons isu-isu yang berkembang, serta implikasinya terhadap pemahaman keagamaan di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode historis dan analisis data digital. Data tren pencarian hadis dikumpulkan melalui Google Trends, kemudian dianalisis berdasarkan pola perubahan tema yang muncul setiap tahunnya. Selanjutnya, faktor sosial-politik yang memengaruhi tren tersebut dikaji dengan merujuk pada peristiwa nasional yang terjadi dalam kurun waktu yang bersamaan. Hasil penelitian menunjukkan bahwa tren pencarian hadis mengalami peningkatan signifikan pada periode tertentu yang berkaitan dengan peristiwa politik, kebijakan pemerintah, serta isu-isu sosial keagamaan. Tema yang dominan dalam pencarian mencakup kepemimpinan, etika sosial, dan toleransi, yang mencerminkan kebutuhan masyarakat terhadap landasan moral dalam menghadapi tantangan sosial-politik. Temuan ini menegaskan bahwa digitalisasi telah mengubah cara masyarakat mengakses dan memahami hadis, sehingga diperlukan upaya literasi digital dan keagamaan untuk memastikan interpretasi yang tepat dan kontekstual.]